(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Nanotechnology, utilising atomic scale substance tailoring, is anticipated to open new ways to tackle and avoid disease. Metallic nanoparticles, which exhibit enhanced chemical activity due to their broad surface to volume ratios and crystallographic surface structure, are among the most promising nanomaterials with antibacterial properties. Taking into account the recent rise in new resistant strains of bacteria to the most active antibiotics, the analysis of bactericidal nanomaterials is especially timely. Study into the well-known action of silver ions and silver-based materials, like silver nanoparticles, has been urged. The present research studies the impact of silver nanoparticles in the range of 1-100 nm on Gram-negative bacteria utilising Scanning Transmission Electron Microscopy (STEM) high angle annular dark field (HAADF). Our observations suggest that the nanoparticles’ bactericidal properties are size-dependent, since the only nanoparticles that have a direct contact with the bacteria preferentially have a diameter of around 1-10 nm.